Systematic Literature Review: Integrasi Etnomatematika dalam Pembelajaran Geometri - Rasyidin, Helmi Hananah; Nur, Fitriani (Jurnal Riset Pembelajaran Matematika, 2025)
Indonesian local culture contains various elements that can be utilized as media for mathematics learning, particularly in the field of geometry. This study aims to analyze geometric concepts in Indonesian local culture. The method used is Systematic Literature Review (SLR). Data collection was conducted by documenting and analyzing relevant articles on ethnomathematics published between 2019 and 2024. A total of 13 nationally accredited journal articles obtained from the Google Scholar and Scopus databases were used in this study. The findings indicate that various geometric concepts, such as flat shapes (squares, triangles, trapezoids), solid shapes (cylinders, blocks), and geometric transformations (symmetry, rotation), are found in various aspects of Indonesian local culture, including art, architecture, and traditional crafts. Based on the results, a variety of geometric concepts embedded in Indonesian local culture were identified. These findings suggest that Indonesian local culture can be utilized by teachers as a contextual and relevant medium for teaching geometry.